Effect of salinity on the biochemical characteristics and antioxidant activity of exopolysaccharide of Porphyridium purpureum FACHB 806 - Li, Qianmei; Chen, Yi; Liu, Xuan; Li, Yi; Xu, Jin; Li, Tao; Xiang, Wenzhou; Li, Aifen (Frontiers in Marine Science, 2023)
Porphyridium exopolysaccharide (EPS) is a kind of high-value biopolymer with various biological activities secreted by microalgae belonging to Porphyridium genus. Salinity is one of the important environmental factors affecting the growth of microalgae. In order to study the effect of salinity, the yield, biochemical characteristics and antioxidant activity of EPS in Porphyridium purpureum FACHB 806 cultured at four salinity levels (5‰, 20‰, 35‰ and 50‰) were investigated in this study. The results demonstrated that P. purpureum FACHB 806 could grow at all salinity levels. The highest cell density and EPS yield were 6.6 × 107 cells·mL-1 and 29.1 pg·cell-1, which were obtained in the 20‰ and 50‰ salinity, respectively. With the increase of salinity, the percentage of xylose and galactose decreased while the percentage of glucose increased. Among all salinity levels, the 5‰ salinity group achieved the maximum contents of total carbohydrate and uronic acid of EPS, and the 50‰ salinity obtained the highest protein content of EPS. Compared to the 20‰ and 35‰ salinity groups, EPS of the 5‰ and 50‰ salinity showed stronger hydroxyl radical scavenging ability. These results indicated that salinity could influence the yield, biochemical composition and antioxidant activity of EPS, which will provide a new strategy to improve the yield and antioxidant activity of EPS.